Air Knife Drying System Application In Removing Pesticides On The Skin Of Fruit - Nurdiana binti Zainal, Nurdiana (2010)
The use of air knife drying system in food industries can be extended to remove pesticides residue on the skin of the fruit. AKD machine will be used first to remove pesticides on the skin of fruit and then to dry the fruits.